Investigating the effect of a passive trunk exoskeleton on local discomfort, perceived effort and spatial distribution of back muscles activity. Issue 11 (2nd November 2021) - Giustetto, Ambra; Vieira Dos Anjos, Fabio; Gallo, Francesca; Monferino, Rossella; Cerone, Giacinto Luigi; Di Pardo, Massimo; Gazzoni, Marco; Micheletti Cremasco, Margherita
Abstract: This study aimed at determining the effect of a passive exoskeleton on local perceived discomfort, perceived effort and low back muscles' activity. Thirteen volunteers performed two simulated working tasks with and without the exoskeleton. In the static task, the exoskeleton decreased the lumbar perceived discomfort, the perceived effort and the level of low back muscles' activity (∼10%) while increasing discomfort in the chest and feet. The percent decrease in EMG amplitude was correlated with the percent increase in perceived effort with exoskeleton. For the dynamic task, the exoskeleton increased the discomfort in the chest and decreased the level of back muscle activity (∼5%). Current findings suggest exoskeleton is effective in reducing the back load while increasing the perceived discomfort at non-targeted body regions in both working tasks. The concurrent increase of discomfort in non-targeted areas probably led to a higher perceived effort despite the reduction of low back muscle activity. Practitioner summary: This study provided insights into exoskeleton effects on local discomfort, perceived effort and muscle activity. Overall, the potential benefits of passive exoskeleton should be considered alongside its adverse effects on the non-targeted body regions that can lead to an increase of perceived effort despite the reduction of back muscle activity.